2015
DOI: 10.1002/lary.25538
|View full text |Cite|
|
Sign up to set email alerts
|

Recurrent laryngeal nerve reinnervation in children: Acoustic and endoscopic characteristics pre‐intervention and post‐intervention. A comparison of treatment options

Abstract: This study presents one of the largest studies of pediatric vocal fold paralysis diagnosis and treatment. The study looks at the spectrum of function in patients with UVCP and looks at the outcomes of options: no treatment, injection laryngoplasty, and ANSA-RLN. Although surgical outcomes vary, both injection laryngoplasty and ANSA-RLN show benefit in laryngeal function, voice stability, voice capacity, perceptual rating, and pVHI scores. Both injection laryngoplasty and ANSA-RLN showed improvements post-treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 19 publications
2
51
1
1
Order By: Relevance
“…It has been our observation and that of others that for some patients the vocal recovery is gradual, but others experience a more abrupt onset of voice improvement that can be pinpointed to within a week or two . A similarly discrete onset of voice improvement is also noted by patients who undergo ansa cervicalis‐recurrent laryngeal nerve (RLN) reinnervation, many of whom report a transition of around 3 months postoperatively . In either case, the sudden vocal improvement likely reflects a sufficient number of regenerating axons simultaneously reaching the laryngeal adductors to produce a noticeable gain in vocal function.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…It has been our observation and that of others that for some patients the vocal recovery is gradual, but others experience a more abrupt onset of voice improvement that can be pinpointed to within a week or two . A similarly discrete onset of voice improvement is also noted by patients who undergo ansa cervicalis‐recurrent laryngeal nerve (RLN) reinnervation, many of whom report a transition of around 3 months postoperatively . In either case, the sudden vocal improvement likely reflects a sufficient number of regenerating axons simultaneously reaching the laryngeal adductors to produce a noticeable gain in vocal function.…”
Section: Introductionmentioning
confidence: 82%
“…2 A similarly discrete onset of voice improvement is also noted by patients who undergo ansa cervicalis-recurrent laryngeal nerve (RLN) reinnervation, many of whom report a transition of around 3 months postoperatively. [10][11][12][13] In either case, the sudden vocal improvement likely reflects a sufficient number of regenerating axons simultaneously reaching the laryngeal adductors to produce a noticeable gain in vocal function. The time from the onset of voice loss to the onset of voice improvement therefore can be regarded as a surrogate marker for the kinetics of RLN regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…They found no correlation with age at surgery, but there was a slight negative correlation in duration between injury and time of surgery [52••]. Zur and Carroll found that recurrent laryngeal nerve innervation has better acoustic, stroboscopic, and perceptual results than injection or observation [51]. At our center, laryngeal EMG is used before any reinnervation procedure, to assess the tracing for lack of motor unit potentials.…”
Section: Laryngeal Reinnervationmentioning
confidence: 99%
“…Various approaches to management have been described for unilateral vocal fold immobility (UVFI) in the pediatric population. Options include injection medialization laryngoplasty (IML), thyroplasty, and ansa‐to‐recurrent laryngeal nerve reinnervation (ANSA‐RLN) . ANSA‐RLN has emerged over the past decade as an effective option and is gaining popularity .…”
Section: Introductionmentioning
confidence: 99%
“…Options include injection medialization laryngoplasty (IML), thyroplasty, and ansa-to-recurrent laryngeal nerve reinnervation (ANSA-RLN). 1 ANSA-RLN has emerged over the past decade as an effective option and is gaining popularity. [2][3][4][5] A recent survey of the American Society of Pediatric Otolaryngology pediatric laryngology working group revealed that in the setting of a longstanding iatrogenic UVFI, 22% and 37% would offer ANSA-RLN and concomitant IML as a first line therapy in young children and teenagers, respectively.…”
Section: Introductionmentioning
confidence: 99%